High Fasting Insulin Levels and Insulin Resistance May Be Linked to Idiopathic Recurrent Pregnancy Loss: A Case-Control Study - Corina-Alina Ispasoiu; Radu Chicea; Florin Vasile Stamatian; Florin Ispasoiu (International Journal of Endocrinology)
Objective. Patients with more than two spontaneous pregnancy losses are diagnosed with recurrent pregnancy loss. The aim of this study was to evaluate the IR (insulin resistance) in patients with idiopathic recurrent pregnancy loss. Material and Method. A single center, case control study was performed on one hundred eighteen women divided into case group (with at least two pregnancy losses, earlier than 20 weeks of gestation, and negative for the recurrent pregnancy loss testing) and control group (with at least one live birth, no pregnancy loss). FG (fasting glucose) and FI (fasting insulin) were determined for all patients. IR was evaluated by HOMA-IR index. Results. There were not significant differences between the mean age and BMI in cases and controls (). Fasting glucose was significantly higher in the control group (85.6 versus 79.8 ), but fasting insulin (15.24 versus 12.83, ) and HOMA-IR (2.98 versus 2.69, ) were significantly higher in the case group. Conclusion. In women with idiopathic recurrent pregnancy loss FI and IR are higher than those in women without spontaneous abortion.